Atopidae (Trilobita) in the upper Marianian (Cambrian Series 2, Stage 4) of Iberia. (January 2021) - Collantes, Luis; Mayoral, Eduardo; Liñán, Eladio; Gozalo, Rodolfo
Abstract: New atopid trilobites are described from the early Cambrian Cumbres beds and Herrerías shale of northern Huelva Province (Andalusia, Spain) and are dated as middle–late Marianian (Cambrian Series 2, Stage 4). New specimens of Atops calanus Richter and Richter, 1941 are described and the Laurentian species Pseudatops reticulatus (Walcott, 1890b ) is recognized for the first time in the Mediterranean subprovince. The associated trilobite assemblage studied herein suggests an age close to the base of Cambrian Stage 4.